Targeted fluorescent optical nanosensors for imaging and measuring function in intracellular microdomains - Coupland, Paul (2008)
Nanosensors offer the opportunity to measure intracellular domains with minimal chemical or physical perturbation. Typically only 60 nm in diameter and synthesised from polymer matrices they entrap chemical sensing elements and can be surface functionalised allowing for further chemical modification. Upon intracellular localisation the cellular environment can be monitored using conventional techniques such as confocal laser scanning microscopy. Reported here is one use of nanosensors to investigate the mechanisms of intracellular delivery mediated via the cell penetrating peptide, Tat. It is shown that information obtained from the nanosensors reveals that the post-delivery environment is representative of a lysosome in terms of both pH and morphology. The delivery mechanism of Tat, however, is shown to be dependent upon the cargo being delivered, corresponding to the absence or presence of a body of polymer matrix; thus nanosensors have been used to further the understanding of the cell penetrating mechanisms of Tat peptide. Technological aspects of nanosensor development have been investigated including polymer matrix modification and different methods of incorporating fluorophores into the nanosensor body. Addressing nanosensors located in an intracellular domain has historically been achieved with epi-fluorescent and confocal microscopy acquiring data from individual or low numbers of cells only. Reported here is the combination of nanosensors with flow cytometry as a technique for en masse investigation into entire cell populations.